Sewage sludge as a renewable resource for citric acid production:optimization of supplementary nutrients - Mohamad Hanapi, Nur Hanis; Alam, Md. Zahangir; Abdul Karim, Mohamed Ismail (Asian Network for Scientific Information, 2011)
The optimization of supplementary nutrients in the sewage sludge as a basal medium was carried out to determine the media components on the citric acid production. Two statistical designs were employed in the citric acid productions which are Plackett-Burman and central composite design (CCD). For the media screening, the two-level Plackett-Burman was applied. Under the experimental conditions, it was observed that total suspended solids of sewage sludge (TSS), sugar, cassava, methanol, potassium di-hydrogen phosphate and urea to be the major factors in maximizing citric acid production. A study of single factor was conducted to find the optimum ranges of parameters for citric acid production followed by the central composite design (CCD) under the responses surface methodology. A polynomial model was created to correlate the relationship between two factors (sewage sludge TSS and sugar) and citric acid production. The optimum yield of citric acid, 29.12 g/L was produced with 0.8% TSS sewage sludge and 7% sugar in four days of fermentation. The determination of coefficient (R2) from the analysis was 0.9527, indicating that the model of this experiment is significant.